A Systematic Literature Review on Cultural Arts Education and the Cultivation of Cultural Values - Zufriady Zufriady; Otang Kurniaman; Suarman Suarman; Nur Islami; Munjiatun Munjiatun (Ignatianum University Press, 2024)
Objectives of the research: This study investigates art education as a means of cultivating cultural values and aims to address questions regarding the methodologies employed in previous research on cultural values. The research presented herein constitutes a Systematic Literature Review (SLR) on cultural education, utilizing the PRISM method adopted in 2020. Research methods: This article conducts a Systematic Literature Review (SLR) on cultural education using the PRISM method adopted in 2020. The search was conducted using Perish or Publish (PoP) for Scopus-indexed international journals and the Garuda portal from the Ministry of Education and Culture, focusing on journals indexed in Sinta. Contextual Background: Because the cultural processes continually evolve in response to the forces that influence culture, cultural acculturation serves as a foundation for arts and cultural workers' efforts to inculcate the values of local wisdom within educational settings. Research findings: Data collection spanned from 2010 to 2022, resulting in the retrieval of 14 international articles and 16 national articles based on their titles and abstracts, totaling 30 articles. These articles originated from various countries, including Belgium, the Czech Republic, Germany, Korea, Poland, Taiwan, China, Istanbul, Slovenia, Turkey, Estonia, and Indonesia. Analysis of the articles revealed that music arts education constituted 27%, arts and culture 33%, local wisdom 14%, dance education 17%, art education 3%, and theatre education 3%. In terms of research methodologies, the study identified action research at 5%, Research and Development at 10%, quantitative research at 10%, qualitative case study research at 7%, literature review at 7%, and qualitative research at 56%. Conclusions and recommendations: Through this SLR, the researcher aims to pave the way for future in-depth research in arts and culture education or for exploring novel approaches.